Hepatocyte Growth Factor Isoforms in Tissue Repair, Cancer, and Fibrotic Remodeling - Ognoon Mungunsukh; Elizabeth A. McCart; Regina M. Day (Biomedicines, 2014)
Hepatocyte growth factor (HGF), also known as scatter factor (SF), is a pleotropic factor required for normal organ development during embryogenesis. In the adult, basal expression of HGF maintains tissue homeostasis and is up-regulated in response to tissue injury. HGF expression is necessary for the proliferation, migration, and survival of epithelial and endothelial cells involved in tissue repair in a variety of organs, including heart, lung, kidney, liver, brain, and skin. The administration of full length HGF, either as a protein or using exogenous expression methodologies, increases tissue repair in animal models of tissue injury and increases angiogenesis. Full length HGF is comprised of an N-terminal hairpin turn, four kringle domains, and a serine protease-like domain. Several naturally occurring alternatively spliced isoforms of HGF were also identified. The NK1 variant contains the N-terminal hairpin and the first kringle domain, and the NK2 variant extends through the second kringle domain. These alternatively spliced forms of HGF activate the same receptor, MET, but they differ from the full length protein in their cellular activities and their biological functions. Here, we review the species-specific expression of the HGF isoforms, their regulation, the signal transduction pathways they activate, and their biological activities.